Pacifism, politics, and feminism : intersections and innovations - Kling, Jennifer, 1984 - (Value Inquiry Book Series, 2019)
Pacifism, Politics, and Feminism: Intersections and Innovations discusses a) how feminist analyses allow for and encourage the re-conceptualization of concepts and ideas once thought familiar from traditional ethical and political philosophy, and b) traditional political topics and issues through pacifist and feminist lenses. The chapters that focus on the former explore the possibility of "queering" such concepts as autonomy, violence, resistance, peace, religion, and politics, while the chapters that focus on the latter bring feminist and pacifist sensibilities and arguments to bear on classic political questions such as when and how violence and war are justified, the appropriateness of various responses to climate change, and the correct way to engage with such topics and themes in educational, institutional settings. Contributors are David Boersema, Barrett Emerick, Tamara Fakhoury, Jane Hall Fitz-Gibbon, William C. Gay, Jennifer Kling, John Lawless, Megan Mitchell, and Harry van der Linden.